Adaptive filter based current controller for Shunt Active filter - Sriranjani, R; Jayalalitha, S (International Journal of Engineering and Technology, 2018)
This paper deals with the harmonic mitigation and reactive power compensation using Shunt Active filter. The performance of the Shunt active filter depends on the design and current control technique for generating a reference current. The design of the filter involves the iterative procedure for choosing the filter components so that it compensates the harmonics and reactive power for maximum load condition. The current controller method adopted for indirect current control technique where the reference signal is similar to the supply current signal. The Adaptive filter used in current controller mitigates harmonics and reactive power and voltage control loop of SAF balancing the active power between the load and supply unit. The learning rate is fixed by repeated simulation. The SAF active filter is tested in four load condition ie., nonlinear load(37% Total Harmonic Distortion(THD)),highly nonlinear load(>100% THD), linear load(<8% THD, power factor(pf) <0.5) and both nonlinear and linear load(37% THD and 0.7 pf). The study is carried out in MATLAB Simulink and the results are presented. Â Â